Rapid detection and cellular fluorescence imaging of the TBI biomarker Let-7i using a DNA–AgNC nanoprobe. (9th May 2019) - Li, Xingmei; Han, Leiming; Guo, Yadong; Chang, Yunfeng; Yan, Jie; Wang, Yong; Li, Na; Ding, Yanjun; Cai, Jifeng
Abstract : Rapid fluorescence detection of Let-7i for TBI diagnosis and intracellular imaging have been studied using the multifunctional DNA–AgNCs. Abstract : Traumatic brain injury (TBI), known as intracranial injury, has been a serious threat to human health. The nonspecific and variable symptoms of TBI have motivated extensive research on miRNAs that serve as significant biomarkers for the TBI diagnosis. However, the current detection methods of TBI miRNAs are conducted only at the in vitro level and involve complex operation systems. Herein, we proposed a novel fluorescence biosensing strategy for cell imaging and rapid detection of Let-7i (a kind of TBI-related miRNAs) based on DNA-functionalized silver nanoclusters (DNA–AgNCs). Moreover, a self-designed DNA–AgNC nanoprobe was fabricated using a hairpin-structured oligonucleotide template to improve the sensitivity and photostability of DNA–AgNCs; in the presence of Let-7i, the strong fluorescence of DNA–AgNCs was quickly switched off, and the entire quantitative analysis process could be completed within 1 h. Cell viability studies demonstrated satisfactorily low cytotoxicity of the DNA-based nanoprobe for HeLa cells. Moreover, confocal fluorescence imaging presented obvious color brightness differences in the HeLa cells before and after Let-7i transfection; this indicated that fluorescence imaging by the proposed nanoprobe might indirectly reflect the levels of cellular Let-7i. Based on the abovementioned investigations, it can be concluded that the Let-7i biosensing method based on the multifunctional DNA–AgNCs may provide a promising strategy for TBI biomarker detection and a bioimaging tool.